2015
DOI: 10.1111/hepr.12563
|View full text |Cite
|
Sign up to set email alerts
|

Carnosic acid protects normal mouse hepatocytes against H2O2‐induced cytotoxicity via sirtuin 1‐mediated signaling

Abstract: Our data indicate that CA protects against oxidative stress-induced cytotoxicity via SIRT1 by regulating subsequent downstream factors such as ERK1/2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…33 It should be noted that although this study indicates that CA is absorbed into the bloodstream and is therefore bioavailable, the in vivo toxicity of such plasma levels is not known. In an in vitro study, CA at 10 μmol/L induced cytotoxicity in primary mouse hepatocytes but at lower concentrations (1 μmol/L) did not have any toxic effect 34 indicating that low CA concentrations, such as those used in the present study, should be preferred to avoid toxicity. More studies in animals and humans should be performed to find the oral doses of CA required for a beneficial effect without any observed toxicity.…”
Section: Discussionmentioning
confidence: 64%
“…33 It should be noted that although this study indicates that CA is absorbed into the bloodstream and is therefore bioavailable, the in vivo toxicity of such plasma levels is not known. In an in vitro study, CA at 10 μmol/L induced cytotoxicity in primary mouse hepatocytes but at lower concentrations (1 μmol/L) did not have any toxic effect 34 indicating that low CA concentrations, such as those used in the present study, should be preferred to avoid toxicity. More studies in animals and humans should be performed to find the oral doses of CA required for a beneficial effect without any observed toxicity.…”
Section: Discussionmentioning
confidence: 64%
“…However, these pathological processes were significantly inhibited by carnosic acid. Many studies have shown that the compound induces apoptosis in cancer cells [54] However, some studies have revealed the anti-apoptotic effect of carnosic acid on normal cells in inflammatory conditions [55][56][57][58][59]. In animal models of several inflammatory diseases, carnosic acid inhibited apoptosis to ameliorate inflammation and tissue injury [48,59,60].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CA (1 μM) enhanced the protein level of sirtuin (SIRT)1, and SIRT1 (siRNA) alleviated the protective role of CA against H 2 O 2 ‐induced cell death. Moreover, H 2 O 2 mediated phosphorylation of extracellular signal regulated kinase 1 and 2 (ERK1/2) in primary hepatocytes could be inhibited by CA . These data indicated that the protective role of CA against H 2 O 2 ‐induced cytotoxicity probably mediates by SIRT1 via regulating the activation of ERK1/2.…”
mentioning
confidence: 86%